2016
DOI: 10.1038/bjc.2016.411
|View full text |Cite
|
Sign up to set email alerts
|

Increased micronucleus frequency in peripheral blood lymphocytes predicts the risk of bladder cancer

Abstract: Background:Bladder cancer (BC) is among the most common malignancies worldwide. The identification of new biomarkers for early BC detection, recurrence/progression is urgently needed. The cytokinesis-block micronucleus assay (CBMN) evaluates chromosome damage in cultured human lymphocytes and micronuclei (MN) provide a convenient and reliable index of both chromosome breakage and loss.Methods:Chromosomal damage (expressed as frequencies of MN, nucleoplasmic bridges and nuclear buds (NBUD)) was evaluated by CBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 44 publications
2
23
1
Order By: Relevance
“…Another explanation may involve the genomic instability present in individuals developing BC. The existence of genomic instability is supported by the fact that BC patients present elevated frequency of MN not only in urothelial cells, but also in other cell types such as lymphocytes (Pardini et al, ), and oral mucosa cells (Feki‐Tounsi et al, ). The existence of genomic instability in these patients has been already proposed suggesting the existence of genetic unstable cells in the normal appearing urotelium of resected patients (Gontijo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another explanation may involve the genomic instability present in individuals developing BC. The existence of genomic instability is supported by the fact that BC patients present elevated frequency of MN not only in urothelial cells, but also in other cell types such as lymphocytes (Pardini et al, ), and oral mucosa cells (Feki‐Tounsi et al, ). The existence of genomic instability in these patients has been already proposed suggesting the existence of genetic unstable cells in the normal appearing urotelium of resected patients (Gontijo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The elevated incidence of this pathology has move many researchers to look for biomarkers of early detection of its recurrence/progression. In this way, a recent association study has shown that MN in PBL is a suitable biomarker of BC risk, since MN frequencies were significantly higher in BC patients than in controls (Pardini et al, ). Nevertheless, MN frequency in PBL is considered a general biomarker more than a specific one of a particular type of cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that MN is a highly useful biomarker to assess genotoxicity, e.g. to benzene (Angelini et al 2016) and MN frequencies were associated with risk of cancer (Lovreglio et al 2014;Pardini et al 2017;Zhang et al 2019). Our study shows significant and dosedependent increase of MN frequencies among workers with very low exposure doses to benzene.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, numerous cytological studies have identified micronuclei within various cancer contexts including head and neck, ovarian, and breast cancers [9][10][11]. Interestingly, the presence of micronuclei in precursor lesions is associated with an increased risk of developing certain cancers [12][13][14][15], suggesting that the presence and frequency of micronuclei may hold clinical value as diagnostic and prognostic biomarkers. Thus, the ability to accurately identify and enumerate micronuclei is relevant in both laboratory and clinical settings.…”
Section: Introductionmentioning
confidence: 99%